2022
DOI: 10.1371/journal.pone.0262040
|View full text |Cite|
|
Sign up to set email alerts
|

Novel insights into Pinus species plastids genome through phylogenetic relationships and repeat sequence analysis

Abstract: Pinus is one of the most economical and ecological important conifers, model specie for studying sequence divergence and molecular phylogeney of gymnosperms. The less availability of information for genome resources enable researchers to conduct evolutionary studies of Pinus species. To improve understanding, we firstly reported, previously released chloroplast genome of 72 Pinus species, the sequence variations, phylogenetic relationships and genome divergence among Pinus species. The results displayed 7 dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In addition, it has relatively high genetic variation; therefore, it is often employed to infer the genetic relationships of species, estimate their differentiation time [12][13][14][15], and sometimes identify germplasm [16]. For example, Zeb et al compared the cp genomes of twenty-four Pinus species and identified a total of thirteen divergent hotspot regions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has relatively high genetic variation; therefore, it is often employed to infer the genetic relationships of species, estimate their differentiation time [12][13][14][15], and sometimes identify germplasm [16]. For example, Zeb et al compared the cp genomes of twenty-four Pinus species and identified a total of thirteen divergent hotspot regions.…”
Section: Introductionmentioning
confidence: 99%
“…The PLOS ONE Editors retract this article [ 1 ] because it was identified as one of a series of submissions for which we have concerns about authorship, competing interests, and peer review. We regret that the issues were not addressed prior to the article’s publication.…”
mentioning
confidence: 99%